Karakterisasi Senyawa Penghambat Polimerisasi Heme Dari Ekstrak Etanol Buah Pare (Momordica charantia L.) - Purwaning Nugroho Widiyati; Syamsudin Syamsudin; Partomuan Simanjuntak (Faculty of Pharmacy, Universitas Muslim Indonesia, 2023)
Malaria, which is caused by a parasitic infection of the genus Plasmodium, is still reported as a disease that contributes a high mortality rate in the world. However, there is another problem currently being faced, namely the incidence of patient resistance to antimalarial drugs on the market, causing an urgent need to develop new antimalarial drugs that are safe and inexpensive. Research on the ethanol extract of bitter melon (Momordica charantia L.) was carried out with the aim of providing information as an alternative antimalarial drug based on the mechanism of heme polymerization inhibition according to the method of Huy et. al and to identify the compound isolate fraction which is predicted to have the antimalarial activity. The ethanol extract of bitter melon (Momordica charantia L.) was prepared by maceration method using 96% pharmaceutical grade ethanol, partitioned using ethyl acetate and distilled water. Part of the partition which was soluble in ethyl acetate was fractionated using column chromatography (SiO2; i. n-hexane-ethyl acetate = 10 : 1 1 : 1; CH2Cl2-MeOH = 10 : 1 1 : 1 The results of heme polymerization inhibition test obtained isolate fraction 8.5 which had the highest activity, namely IC50 302.78 ppm and IC50 (chloroquine diphosphate as a positive control IC50 218.71 ppm).The results of identification by LCMS/MS spectroscopy showed that isolate fraction 8.5 contained several chemical compounds such as momordicoside L; momordicoside I and momordicoside F2 and quercetin The chemical compound that is predicted to play a role in inhibiting Heme polymerization is quercetin